O sofrimento psíquico do policial civil [manuscrito]: uma leitura psicanalítica - Queiroz, Maria do Socorro (2008)
The discourses produced by the policemen related to the psychic suffering, as well as the position which they occupy in their own discourses, are object of examination in this dissertation. The analysis here presented was conducted based in semi structured interviews with four Civil Policemen who had been previously conducted to be monitored in the Medical Assistance and Psychosocial Department of the Civil Police of Ceará. Our analysis, anchored in the psychoanalytical theory, made possible to find out that our interviewees emerged from the policial group with their collective and individual signifiers and their various forms of suffering through the exteriorization of the symptoms. In our investigation it was also possible to recognize that it is impossible to pledge a direct cause and effect relation between the policial activity and the related psychic suffering. On the other hand, it is possible to assure that the psychic suffering manifests itself through various symptoms, unconsciously overdetermined, which are in intimate connection with the interviewees’ stories of life. In relation to the interviewees’ discursive positions in face of the related suffering, it was observed, predominantly, a hysterical discourse, which is moved by a desire of understanding. Lastly, when considering the results according to the psychoanalytical reinvention of the subject, we can guarantee that the policial institution may consist in a proper place for the psychoanalytical hearing.